Antifungal Susceptibility of Candida albicans Biofilms under Hyperbaric Conditions - Tourville, Claudia; Rigden, Gabrielle; Bailey-Hartse, Scott (My University, 2018)
Candia albicans is a fungus notorious for infection of indwelling medical devices and inflamed tissues in immunocompromised patients. Its unique ability to form biofilms, or scaffold-like networks, makes it increasingly resistant towards treatment. Multiple classes of antifungal drugs have been developed for treatment, but each demonstrates its own threat towards patient recovery and future quality of life. Despite extensive research focused on Candida species, few have thoroughly investigated the influence of oxygen availability on biofilm formation and drug resistance. Hypoxia, or oxygen depletion, is common at sites of infection and has been identified as a potential stimulant of extracellular matrix (ECM) production. ECM material assists formation of the biofilm while providing a protective coat to block antifungals from accessing the fungal cellular membrane. In this research, we explore the effects of high-pressure oxygen (hyperbaric) conditions on the development of biofilms and susceptibility towards polyene, triazole, and echinocandin antifungals. Advanced confocal microscopy techniques have allowed us to assess the viability and morphology of biofilms in response to drug treatment simultaneously. With approximately 46,000 cases of Candida infections annually in the US, this simple approach towards improved outcomes has the potential to be both far-reaching and easily accessible to many in need.
Color poster with text and images.
Keywords: Candida Albicans; Biofilms; Hyperbaric oxygen therapy; Posters